THE ROLE OF EDUCATION AND EDUCATION IN THE SPIRITUALITY OF YOUTH (Conferencea, 2022)
In this article we will talk about raising the spirituality of our young people in the years of Independence, reaching adulthood as owners of high intelligence, able to compete freely in the conditions of a market economy, carefully mastering modern knowledge it is said about the role of education and training